Practices Before Policy: Research Data Management Behaviours in Canada - Cheung, Melissa; Cooper, Alexandra; Dearborn, Dylanne; Hill, Elizabeth; Johnson, Erin; Mitchell, Marjorie; Thompson, Kristi (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2022)
In anticipation of the then forthcoming Tri-Agency Research Data Management Policy, a consortium of professionals from Canadian university libraries surveyed researchers on their research data management (RDM) practices, attitudes, and interest in data management services. Data collected from three surveys targeting researchers in science and engineering, humanities and social sciences, and health sciences and medicine were compiled to create a national dataset. The present study is the first large-scale survey investigating researcher RDM practices in Canada, and one of the few recent multi-institutional and multidisciplinary surveys on this topic. This article presents the results of the survey to assess researcher readiness to meet RDM policy requirements, namely the preparation of data management plans (DMPs) and data deposit in a digital repository. The survey results also highlight common trends across the country while revealing differences in practices and attitudes between disciplines. Based on our survey results, most researchers would have to change their RDM behaviors to meet Tri-Agency RDM policy requirements. The data we gathered provides insights that can help institutions prioritize service development and infrastructure that will meet researcher needs.